MODELAGEM MATEMÁTICA E COMPUTACIONAL DE UM BIODIGESTOR - PASQUALETTO SCHMAEDECKE , PEDRO; DE FATIMA BRONDANI BINELO , MARCIA; OBREGON , LUANA; DE CAMPOS , MAURÍCIO; MANOEL LENZ VIANNA DA SILVA , JOÃO (Salão do Conhecimento, 2021)
Trabalho de IC de projeto pesquisa desenvolvido na Unijuí